Assessing online education during the COVID-19 pandemic: a survey of lecturers in Ukraine - Bakhmat, Liudmyla; Babakina, Oksana; Belmaz, Yaroslava (My University, 2021)
The winter and spring of 2020 was a challenging time worldwide. The COVID-19 pandemic seriously affected all spheres of life: from an industrial decline to educational transformations. In order to continue the 2019/2020 academic year, higher educational institutions had to adjust in-class learning to online. This paper aims at assessing the satisfaction and acceptance rate of Ukrainian lecturers with online education, as well as indicating problems and benefits they had singled out. The technical side of online education was also of interest. Therefore, the study employed an online survey to investigate technical support and tools used during the quarantine, advantages and disadvantages of online teaching, the level of satisfaction and acceptance. The findings from the study suggest that lecturers got different levels of technical support and used an assortment of tools to organise online education. The study revealed that the main advantage was time efficiency, while internet connection and technical problems were the most commonplace problems. Other findings of the survey are that lecturers were partially satisfied with online education but showed low acceptance of online education.
Bakhmat L. Assessing online education during the COVID-19 pandemic: a survey of lecturers in Ukraine / L Bakhmat, O. Babakina, Ya. Belmaz // Journal of Physics: Conference Series : IOP Publishing, 2021. – Vol. 1840.
Keywords: екстрене навчання, вища освіта, онлайн-освіта, онлайн -навчання; emergency elearning, higher education, online education, online learning and online teaching; экстренное электронное обучение, высшее образование, онлайн-образование, онлайн-обучение